Oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel capable of rapidly gelling as well as preparation method and application of oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel
By adding sodium periodate and aminophenylboric acid to the sodium alginate/polyvinyl alcohol hydrogel, a rapid gel-forming oxidized sodium alginate/polyvinyl alcohol fluorescent hydrogel is solved by slow and inadequate gel-forming speed. The problem of fluorescence characteristics has achieved efficient hydrogel preparation and is suitable for medical and fluorescent anti-counterfeiting materials.
Patent Information
- Application Number
- CN202411309178.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The existing sodium alginate/polyvinyl alcohol hydrogels have slow glue formation speed and do not have fluorescence characteristics, which limits their application in the fields of anti-counterfeiting and imaging.
By adding sodium periodate to the aqueous solution of sodium alginate, then reacting with aminophenylboric acid and activator, it produces phenylboric acid-based oxidized sodium alginate, and mixes with polyvinyl alcohol solution, and quickly stirs to form oxidized sodium alginate/ Polyvinyl alcohol fluorescent hydrogel.
The rapid gel formation of hydrogels is achieved (within 20s), with three-dimensional porous structure, excellent swelling performance, fluorescence characteristics, pH response and reactive oxygen response, broadening its application range in medical materials and fluorescent anti-counterfeiting materials.
Smart Images

Figure CN119192611A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogel preparation, and in particular to an oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel capable of rapid gelation, and a preparation method and application thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Hydrogel is a hydrophilic polymer with a three-dimensional cross-linked network structure. Its physical and chemical properties are similar to those of human biological tissues, showing good biocompatibility. Hydrogel can efficiently load and release drugs through its unique swelling, water retention and high permeability properties. At the same time, due to the flexibility and excellent adhesion of hydrogel, it can be used as a wound dressing to promote wound healing.
[0004] Sodium alginate (SA) is a water-soluble anionic biopolymer extracted from natural seaweed or produced by bacteria. It is rich in hydroxyl and carboxyl groups and has strong affinity with dyes and metal ions. However, single-component SA hydrogels have problems such as poor mechanical properties, poor gel forming properties, and poor adsorption stability, which seriously limit their wide application. Polyvinyl alcohol (PVA) is a common linear polyhydroxy polymer with high film-forming ability and chemical stability. It is non-toxic, biodegradable, and water-soluble, and has the inherent advantage of preparing ideal "green" hydrogels; however, single PVA hydrogels are prone to swelling and adhesion, and have poor stability. Combining the two to prepare sodium alginate / polyvinyl alcohol hydrogels can combine the advantages of SA and PVA and solve the problem of poor mechanical properties or stability of single-component hydrogel materials.
[0005] In the prior art, physical crosslinking methods (such as freeze-thaw method and calcium ion crosslinking method) are usually used to prepare SA / PVA composite hydrogels. However, the gelation speed of this method is slow and the production efficiency is low. The existing chemical crosslinking method usually requires specific triggering conditions, such as adding catalysts, applying light, etc., and the gelation speed is also relatively slow. In addition, the existing SA / PVA composite hydrogels usually do not have fluorescent properties, and it is difficult to achieve further application in the fields of anti-counterfeiting, imaging, etc. Therefore, how to provide a method for preparing a sodium alginate / polyvinyl alcohol hydrogel that can quickly gel within 1 minute and has fluorescent properties, so as to efficiently prepare fluorescent hydrogels that can be used in the fields of anti-counterfeiting, imaging, etc., is a problem to be solved urgently. Summary of the invention
[0006] In view of this, the present invention provides a fast-gelling oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel and a preparation method and application thereof, which solves the problem in the prior art that the sodium alginate / polyvinyl alcohol hydrogel has a slow gelling speed and lacks fluorescent properties.
[0007] In a first aspect, the present invention provides a method for preparing a rapidly gelling oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel, comprising the following steps:
[0008] Adding sodium periodate to the sodium alginate aqueous solution for oxidation, dialyzing and drying to obtain oxidized sodium alginate;
[0009] Dissolving oxidized sodium alginate in water, adding aminophenylboronic acid and an activator to react to obtain a phenylboronic acid-based oxidized sodium alginate solution;
[0010] The phenylboronic acid-based oxidized sodium alginate solution is mixed with the polyvinyl alcohol solution and stirred for 8 to 20 seconds to obtain the product.
[0011] Preferably, the concentration of the sodium alginate aqueous solution is 1-3 wt %.
[0012] Preferably, the mass ratio of sodium alginate to sodium periodate is 2:(0.8-1.2).
[0013] Preferably, the oxidation time is 20 to 30 hours, the oxidation temperature is 20 to 30° C., and the oxidation process is carried out in a light-proof condition.
[0014] Preferably, in the step of dissolving oxidized sodium alginate in water, the concentration of oxidized sodium alginate is 1 to 3 wt %.
[0015] Preferably, the aminophenylboronic acid is selected from 3-aminophenylboronic acid or 4-aminophenylboronic acid, and the activator is 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide.
[0016] Preferably, the mass ratio of the oxidized sodium alginate, aminophenylboronic acid and activator is 8:(2-3):(5-6).
[0017] Preferably, the concentration of the polyvinyl alcohol solution is 10-20% w / v.
[0018] Preferably, the volume ratio of the phenylboronic acid-based oxidized sodium alginate solution to the polyvinyl alcohol solution is 1:(0.8-1.2).
[0019] In a second aspect, the present invention provides a rapidly gelling oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel prepared by the above preparation method.
[0020] In a third aspect, the present invention provides the use of the above-mentioned rapidly gelling oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel in the preparation of medical materials for tissue repair or fluorescent anti-counterfeiting materials.
[0021] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0022] (1) The preparation method of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel of the present invention is simple and convenient, the gelation is very rapid (within 20 seconds), no additional catalyst or special conditions such as light are required, the equipment cost is low, and it is suitable for large-scale preparation;
[0023] (2) The rapidly gelling oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel prepared by the present invention has a three-dimensional porous structure, excellent swelling performance, a swelling ratio of up to 460%, and has the potential to load a variety of drugs, cells, growth factors, and promote drug release and wound healing; the hydrogel of the present invention emits blue light under ultraviolet light irradiation, which can realize anti-counterfeiting or imaging functions; at the same time, it has stable properties, has the characteristics of pH response and active oxygen response, and can achieve self-healing, thereby improving the utilization rate of the hydrogel. The hydrogel of the present invention has excellent comprehensive performance and broadens its application range. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 It is a synthetic reaction route of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel of Examples 1 to 3 of the present invention;
[0026] Figure 2 is a scanning electron microscope (SEM) image of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel prepared in Example 2 of the present invention;
[0027] Figure 3 is the relationship between the storage modulus and the frequency of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogels of Examples 1 to 3 of the present invention;
[0028] Figure 4 is the relationship between the storage modulus of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel of Examples 1 to 3 of the present invention and time;
[0029] Figure 5 This is a graph showing the adhesion performance test of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel according to Example 2 of the present invention;
[0030] Figure 6 is the swelling ratio of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel prepared in Examples 1 to 3 of the present invention;
[0031] Figure 7 This is a digital picture of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel under ultraviolet light irradiation according to Example 2 of the present invention;
[0032] Figure 8 This is a self-healing performance test diagram of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel of Example 2 of the present invention;
[0033] Fig. 9 is the relationship between the modulus and strain of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogels of Examples 1 to 3 of the present invention;
[0034] Fig.10 These are digital images of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel of Example 2 of the present invention without treatment, under the action of hydrochloric acid, NaOH solution, and H2O2 solution. DETAILED DESCRIPTION
[0035] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0036] The present invention provides a method for preparing a rapidly gelling oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel, comprising the following steps:
[0037] Adding sodium periodate to the sodium alginate aqueous solution for oxidation, dialyzing and drying to obtain oxidized sodium alginate;
[0038] Dissolving oxidized sodium alginate in water, adding aminophenylboronic acid and an activator to react to obtain a phenylboronic acid-based oxidized sodium alginate solution;
[0039] The phenylboronic acid-based oxidized sodium alginate solution is mixed with the polyvinyl alcohol solution and stirred for 8 to 20 seconds to obtain the product.
[0040] The present invention firstly utilizes sodium periodate to oxidize sodium alginate, so that the sodium alginate is oxidized and ring-opened, and the exposed aldehyde group and carboxyl group on the monomer react with aminophenylboronic acid together, so that one monomer can be grafted with up to three phenylboronic acid groups, which not only accelerates the gelation speed of the hydrogel, but also fixes a large number of phenylboronic acid groups on the sodium alginate molecular chain, so that the benzene ring can only vibrate in situ, thereby realizing the fluorescence phenomenon of aggregation-induced emission, so that the hydrogel prepared by the present invention has fluorescent characteristics. The phenylboronic acid group reacts with the hydroxyl group in polyvinyl alcohol to generate a borate ester bond, thereby cross-linking to obtain the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel.
[0041] In the present invention, the concentration of the sodium alginate aqueous solution is 1-3wt%, more preferably 1-2wt%, and most preferably 2wt%. Too high a concentration of the sodium alginate aqueous solution will lead to decreased fluidity, which is not conducive to the oxidation reaction.
[0042] In the present invention, the mass ratio of sodium alginate to sodium periodate is 2:(0.8-1.2). Sodium periodate can oxidize the hydroxyl group in sodium alginate into aldehyde group, which is convenient for reacting with aminophenylboronic acid.
[0043] In the present invention, the oxidation time is 20 to 30 hours, more preferably 23 to 27 hours; the oxidation temperature is 20 to 30°C, and it can be carried out at room temperature. Since sodium periodate is easily decomposed when exposed to light, the oxidation process is carried out under light-proof conditions. After the oxidation is completed, the present invention preferably uses a terminator to terminate the reaction, and the terminator is preferably ethylene glycol.
[0044] The present invention does not impose any special restrictions on the dialysis step, and the dialysis method commonly used in the art can be used. The dialysis is to purify the oxidized sodium alginate and remove unreacted small molecules. The present invention does not impose any special restrictions on the drying step after dialysis, and freeze drying is preferred in the present invention.
[0045] In the present invention, in the step of dissolving oxidized sodium alginate in water, the concentration of oxidized sodium alginate is 1 to 3 wt %, more preferably 1.5 to 2.5 wt %.
[0046] In the present invention, the aminophenylboronic acid is selected from 3-aminophenylboronic acid or 4-aminophenylboronic acid, which reacts with carboxylic acid to form an amide bond, and reacts with an aldehyde group to form a Schiff base, so that one sodium alginate repeating unit is connected to three phenylboronic acid groups. The activator is 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide, which can promote the reaction of amino groups with carboxyl groups or aldehyde groups.
[0047] In the present invention, the mass ratio of the oxidized sodium alginate, aminophenylboronic acid and activator is 8:(2-3):(5-6).
[0048] In the present invention, the concentration of the polyvinyl alcohol solution is 10-20% w / v, and the solvent of the polyvinyl alcohol solution is water. The present invention does not impose any special restrictions on the preparation method thereof, and the preparation method of the polyvinyl alcohol solution commonly used in the art can be adopted. The present invention does not impose any special restrictions on the type of polyvinyl alcohol, for example, polyvinyl alcohol 1799, polyvinyl alcohol 1788, polyvinyl alcohol 2088, polyvinyl alcohol 2099, polyvinyl alcohol 2488, polyvinyl alcohol 2499, etc. can be selected.
[0049] In the present invention, the volume ratio of the phenylboronic acid-oxidized sodium alginate solution to the polyvinyl alcohol solution is 1:(0.8-1.2). The phenylboronic acid groups of the phenylboronic acid-oxidized sodium alginate react with the hydroxyl groups of the polyvinyl alcohol to form a borate ester bond. Since the phenylboronic acid groups of the phenylboronic acid-oxidized sodium alginate are relatively large, they can quickly undergo a cross-linking reaction with the polyvinyl alcohol to form a gel at room temperature.
[0050] The present invention also provides a rapidly gelled oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel prepared by the above-mentioned preparation method. The oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel obtained by the present invention has a three-dimensional porous structure, excellent swelling performance, and a swelling ratio of up to 460%; it emits blue light under ultraviolet light, has the characteristics of pH response and active oxygen response, and can achieve self-healing.
[0051] The present invention also provides the use of the above-mentioned oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel capable of rapidly gelling in the preparation of medical materials for tissue repair or fluorescent anti-counterfeiting materials.
[0052] The technical solution of the present invention is further described below in conjunction with specific embodiments. Figure 1 This is a synthetic reaction route for the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel of Examples 1 to 3.
[0053] Example 1
[0054] This embodiment provides a method for preparing oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel, comprising the following steps:
[0055] (1) Weigh 1.5 g of sodium alginate and dissolve it in 75 mL of deionized water. Stir until completely dissolved. Weigh 0.75 g of sodium periodate and dissolve it in 5 mL of deionized water. Add the sodium periodate solution dropwise to the sodium alginate solution and stir to react for 24 h in the dark. Add 1 mL of ethylene glycol to the above solution to stop oxidation for 2 h, dialysis and purification for 2 days, and freeze-dry to obtain oxidized sodium alginate powder.
[0056] (2) Weigh 80 mg of oxidized sodium alginate powder, dissolve it in 4 mL of deionized water, and stir until it is completely dissolved. Weigh 35 mg of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC), 23 mg of N-hydroxysuccinimide (NHS), and 27 mg of 3-aminophenylboronic acid, add them to the above solution, and stir for 2 h to obtain a phenylboronic acid-based oxidized sodium alginate solution.
[0057] (3) Weigh 1 g of polyvinyl alcohol 1799, dissolve it in 10 mL of deionized water, and heat and stir at 90° C. until it is completely dissolved; thereby obtaining a polyvinyl alcohol solution.
[0058] (4) Take 1 mL of the polyvinyl alcohol solution (10% w / v) of step (3), add 1 mL of the phenylboronic acid-based oxidized sodium alginate solution of step (2), and stir rapidly for 10 seconds to obtain the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel.
[0059] Example 2
[0060] This embodiment provides a method for preparing oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel, comprising the following steps:
[0061] (1) Weigh 1.5 g of sodium alginate and dissolve it in 75 mL of deionized water. Stir until completely dissolved. Weigh 0.75 g of sodium periodate and dissolve it in 5 mL of deionized water. Add the sodium periodate solution dropwise to the sodium alginate solution and stir to react for 24 h in the dark. Add 1 mL of ethylene glycol to the above solution to stop oxidation for 2 h, dialysis and purification for 2 days, and freeze-dry to obtain oxidized sodium alginate powder.
[0062] (2) Weigh 80 mg of oxidized sodium alginate powder, dissolve it in 4 mL of deionized water, and stir until it is completely dissolved. Weigh 35 mg of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, 23 mg of N-hydroxysuccinimide, and 27 mg of 3-aminophenylboronic acid, add them to the above solution, and stir for 2 h to obtain a phenylboronic acid-based oxidized sodium alginate solution.
[0063] (3) Weigh 1.5 g of polyvinyl alcohol 1799, dissolve it in 10 mL of deionized water, and heat and stir at 90° C. until it is completely dissolved; obtain a polyvinyl alcohol solution.
[0064] (4) Take 1 mL of polyvinyl alcohol solution (15% w / v), add 1 mL of phenylboronic acid-based oxidized sodium alginate solution thereto, and stir rapidly for 10 seconds to obtain a fast fluorescent self-healing oxidized sodium alginate / polyvinyl alcohol hydrogel.
[0065] Figure 2 This is a scanning electron microscope (SEM) image of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel prepared in this example. It can be seen that the prepared hydrogel has a rich porous structure, can store a large amount of water, and is an excellent drug carrier.
[0066] Example 3
[0067] This embodiment provides a method for preparing oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel, comprising the following steps:
[0068] (1) Weigh 1.5 g of sodium alginate and dissolve it in 75 mL of deionized water. Stir until completely dissolved. Weigh 0.75 g of sodium periodate and dissolve it in 5 mL of deionized water. Add the sodium periodate solution dropwise to the sodium alginate solution and stir to react for 24 h in the dark. Add 1 mL of ethylene glycol to the above solution to stop oxidation for 2 h, dialysis and purification for 2 days, and freeze-dry to obtain oxidized sodium alginate powder.
[0069] (2) Weigh 80 mg of oxidized sodium alginate powder, dissolve it in 4 mL of deionized water, and stir until it is completely dissolved. Weigh 35 mg of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, 23 mg of N-hydroxysuccinimide, and 27 mg of 3-aminophenylboronic acid, add them to the above solution, and stir for 2 h to obtain a phenylboronic acid-based oxidized sodium alginate solution.
[0070] (3) Weigh 2 g of polyvinyl alcohol 1799, dissolve it in 10 mL of deionized water, and heat and stir at 90° C. until it is completely dissolved; thereby obtaining a polyvinyl alcohol solution.
[0071] (4) Take 1 mL of the polyvinyl alcohol solution (20% w / v) of step (3), add 1 mL of the phenylboronic acid-based oxidized sodium alginate solution thereto, and stir rapidly for 10 seconds to obtain a fast fluorescent self-healing oxidized sodium alginate / polyvinyl alcohol hydrogel.
[0072] Test example
[0073] 1. Rheological test:
[0074] The rheometer strain parameter was set to 1%, the temperature was 25°C, and the scanning frequency range was 0.1-40 Hz, and the relationship between the storage modulus and the frequency of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel of Examples 1 to 3 was obtained, as shown in FIG. Figure 3 shown. Figure 3 In the figure, the storage modulus of hydrogels of various concentrations remains stable with frequency changes, indicating that the internal cross-linking of the hydrogel is completed; the storage modulus of the hydrogel increases with the increase of the concentration of the polyvinyl alcohol solution, indicating that the material preparation can achieve modulus regulation.
[0075] The strain parameter of the rheometer was set to 1%, the temperature was 25°C, the scanning frequency range was 1 Hz, and the rheological test was performed on the mixing process of the phenylboronic acid-based oxidized sodium alginate solution and the polyvinyl alcohol solution to obtain the relationship between the storage modulus of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel of Examples 1 to 3 and the time change, as shown in FIG. Figure 4 shown. Figure 4It was observed that G′ gradually became larger than G″ with increasing time, indicating that the two solutions transformed into a solid gel state. And as the concentration of polyvinyl alcohol decreased, the moment when G′ was larger than G″ became earlier. The reaction time of 10% w / v polyvinyl alcohol solution (Example 1) was even shorter than the instrument reaction time, and the data directly showed the gel state in which G′ was larger than G″.
[0076] 2. Adhesion performance test:
[0077] The adhesion performance test of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel in Example 2 is as follows Figure 5 As shown, Figure 5 In the experiment, the prepared hydrogel was adhered to the finger joints, and as the fingers were bent, the hydrogel adhered tightly to the skin surface.
[0078] 3. Swelling performance test:
[0079] The oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel prepared in Examples 1 to 3 was freeze-dried to constant weight and then weighed. The dry gel was immersed in 10 mL of phosphate buffer (pH = 7.2), taken out at regular intervals, and the surface moisture was carefully absorbed with filter paper, and then the wet weight was weighed to calculate the swelling ratio, such as Figure 6 It can be seen that the swelling ratio of the hydrogel decreases with the increase of the cross-linking agent concentration and can reach more than 400%. The prepared hydrogel has excellent swelling properties.
[0080] 4. Fluorescence performance determination:
[0081] The oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel prepared in Example 2 was used as the test object and irradiated with a 365 nm ultraviolet lamp. Figure 7 As shown, the hydrogel itself is yellow, emits blue light under ultraviolet light, and finally turns green.
[0082] 5. Self-healing performance test:
[0083] A portion of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel prepared in Example 2 was dyed with methylene blue, and the portion was placed in contact with the surface of another portion of the hydrogel. After standing for 10 minutes, the morphology of the hydrogel was observed. Figure 8 As shown, the two parts of the hydrogel become one.
[0084] The hydrogel was subjected to rheological tests to further verify the self-healing properties of the hydrogel. The rheometer scanning frequency was set to 1 Hz, the temperature was 25°C, and the strain parameter range was 1-300%. The relationship between the modulus and strain of the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogels of Examples 1 to 3 was obtained, as shown in FIG. Fig. 9 shown. Fig. 9In the figure, under a low strain state of 1%, G′ was observed to be greater than G″, indicating a solid gel state. Subsequently, a strain of 300% was applied, resulting in a significant decrease in both G′ and G″. In addition, G′ became lower than G″, indicating the collapse of the network structure and the instantaneous transition of the hydrogel from a quasi-solid state to a quasi-liquid state. After reducing the strain to 1%, both G′ and G″ immediately recovered to their original values, indicating that the hydrogel returned to its original solid state, which confirmed the change in the cross-linked network. During the cyclic test, the healing process was completely repeatable and reversible, demonstrating the thixotropy and inherent self-healing properties of the hydrogel.
[0085] 6. pH response and active oxygen response:
[0086] 200 μL of 1M hydrochloric acid, NaOH solution, and H2O2 solution were added to the oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel prepared in Example 2, respectively, and compared with the untreated hydrogel. After standing for 30 minutes, the morphology of the hydrogel was observed. Fig.10 As shown. The untreated blank group hydrogel maintained its original morphology, the hydrogel structure was destroyed by the addition of hydrochloric acid, the hydrogel structure was still maintained by the addition of NaOH solution, and the hydrogel structure was also destroyed by the addition of H2O2 solution. This shows that the prepared fast fluorescent self-healing oxidized sodium alginate / polyvinyl alcohol hydrogel is sensitive to pH, decomposes in an acidic environment, strengthens in an alkaline environment, and decomposes in an active oxygen environment.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a rapidly gelling oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel, characterized in that: The steps include: Adding sodium periodate to the sodium alginate aqueous solution for oxidation, dialyzing and drying to obtain oxidized sodium alginate; Dissolving oxidized sodium alginate in water, adding aminophenylboronic acid and an activator to react to obtain a phenylboronic acid-based oxidized sodium alginate solution; The phenylboronic acid-based oxidized sodium alginate solution is mixed with the polyvinyl alcohol solution and stirred for 8 to 20 seconds to obtain the product.
2. The preparation method according to claim 1, characterized in that The concentration of the sodium alginate aqueous solution is 1-3 wt %.
3. The preparation method according to claim 1, characterized in that: The oxidation time is 20 to 30 hours, the oxidation temperature is 20 to 30° C., and the oxidation process is carried out in a light-proof condition.
4. The preparation method according to claim 1, characterized in that: In the step of dissolving oxidized sodium alginate in water, the concentration of oxidized sodium alginate is 1-3 wt %.
5. The preparation method according to claim 1, characterized in that: The aminophenylboronic acid is selected from 3-aminophenylboronic acid or 4-aminophenylboronic acid, and the activating agent is 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the oxidized sodium alginate, aminophenylboronic acid and activator is 8:(2-3):(5-6).
7. The preparation method according to claim 1, characterized in that: The concentration of the polyvinyl alcohol solution is 10-20% w / v.
8. The preparation method according to claim 1, characterized in that: The volume ratio of the phenylboronic acid-based oxidized sodium alginate solution to the polyvinyl alcohol solution is 1:(0.8-1.2).
9. The rapidly gelling oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the rapidly gelling oxidized sodium alginate / polyvinyl alcohol fluorescent hydrogel according to claim 9 in the preparation of medical materials for tissue repair or fluorescent anti-counterfeiting materials.
Citation Information
Patent Citations
Oxidized sodium alginate / gelatin degradable hydrogel and preparation method thereof
CN102417734A
Medical hydrogel with pH sensitivity, self-healing nature and cell adhesion and preparation method thereof
CN108530651A
Carboxyethyl chitosan / polyvinyl alcohol self-healing hydrogel as well as preparation method and application thereof
CN109517193A
Sodium alginate-dopamine / polyvinyl alcohol hydrogel, and preparation method and application thereof
CN109705369A
Hydrogel cytoskeleton based on natural macromolecules and with adjustable strength and gelling time
CN111704729A
